ANALISIS KEUANGAN USAHA KUB RUMAH JAHIT LESTARI DALAM PENYUSUNAN LAPORAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING - Nur Anita; Armita Novriana Rambe (Politeknik Negeri Bengkalis, 2023)
The purpose of this research is to find how to prepare a report on the cost of production at KUB Rumah Jahit Lestari, in addition to how to report the cost of production at KUB Rumah Jahit Lestari if it is prepared using the full costing method. This study is qualitative and employs a quantitative descriptive method. In-depth interviews and observation were used as data collection techniques. The results revealed that the cost of production per unit was not accurate because it did not account for fixed overhead costs. This research can help MSME actors determine the right selling price for business continuity by transferring knowledge about calculating the cost of production per unit.